Gerakan Masyarakat Sadar Zakat - Abib Novriyanto; Syamsul Hilal (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
The Zakat Aware Community Movement is an initiative to raise Muslims' awareness of the importance of zakat as a religious obligation and socio-economic instrument. The goal is to encourage people to pay zakat, both zakat mal and fitrah, correctly and on target to help the poor and reduce poverty and social inequality. Zakat not only has spiritual value, but also a strategic role in welfare distribution. Awareness of zakat is expected to counter consumptive behavior or hedonism, which in Islam is known as israf (excessive) and tabdzir (wasteful). The concept of “mâl” (wealth) in Islam is everything that can be legally owned and utilized, such as houses, money, gold, and others. Blessed wealth is wealth that is obtained lawfully, benefits others, and is used to get closer to Allah. Islam also pays great attention to poverty, which is described through the terms fakir and miskin. For this reason, zakat as the third pillar of Islam has a major role in overcoming it. For those who are reluctant to pay zakat, Islam recognizes the punishment of ta'zir - a punishment imposed by the ruler to safeguard the public interest. Finally, zakat that is paid consciously and sincerely can bring blessings to wealth, strengthen social solidarity, and strengthen the economic resilience of the people.